Enzymatic processing and MHC loading 2Peptide editing mediated by TAPBPR. (October 2022) - Tudor Ilca, F.; Neerincx, Andreas; Hermann, Clemens; Marcu, Ana; Stevanović, Stefan; Deane, Janet E.; Boyle, Louise H.
Abstract : Objectives: Although tapasin and TAPBPR are known to perform peptide editing on MHC class I molecules, the precise molecular mechanism(s) involved in this process remain largely enigmatic. The recently reported crystal structures of human TAPBPR in complex with mouse MHC class I demonstrated that TAPBPR facilitates peptide exchange by widening the peptide binding groove of MHC class I at the α2–1 region. However, the step-by-step events involved in this process still need to be elucidated. Here, we explored whether the K22-D35 loop of TAPBPR, which is located near the MHC class I F pocket, is involved in peptide editing on MHC class I. Methods: We produced a panel of TAPBPR variants with alterations in the K22-D35 loop and subsequently tested their ability to perform peptide exchange on MHC class I. Immunopeptidomic analysis was used to further explore the impact of mutating the TAPBPR loop on the peptide repertoire presented on MHC class I. Results: We reveal a critical role of the K22-D35 loop of TAPBPR in mediating peptide exchange on MHC I. We identify a specific leucine within this loop that enables TAPBPR to facilitate peptide dissociation from MHC class I. Moreover, we delineate the molecular features of the MHC class I F pocket required for TAPBPR to promote peptide dissociation in a loop-dependent manner. Conclusions: Our data reveal that chaperone-mediated peptide editing on MHC I can occur by different mechanisms dependent on the C-terminal residue that the MHC I accommodates in its F pocket.